The Playful Experiences (PLEX) framework as a guide for expert evaluation - Lucero, Andrés; Holopainen, Jussi; Ollila, Elina; Suomela, Riku; Karapanos, Evangelos (My University, 2013)
The Playful Experiences (PLEX) framework is a categorization of playful experiences based on previous theoretical work on pleasurable experiences, game experiences, emotions, elements of play, and reasons why people play. While the framework has been successfully employed in design-related activities, its potential as an evaluation tool has not yet been studied. In this paper, we apply the PLEX framework in the evaluation of two game prototypes that explored novel physical interactions between mobile devices using Near-Field Communication, by means of three separate studies. Our results suggest that the PLEX framework provides anchor points for evaluators to reflect during heuristic evaluations. More broadly, the framework categories can be used as a checklist to assess different attributes of playfulness of a product or service.
Keywords: Evaluation methods; Heuristic evaluation; Playfulness